Controllability and stabilizability of discontinuous bimodal piecewise linear systems - Le Quang Thuan; Mehmet Kanat Çamlıbel (My University, 2015)
Controllability and stabilizability of discontinuous bimodal piecewise linear systems
Keywords: Controllability; Stabilizability; Piecewise linear